Hubungan Ketaatan Beribadah (Sholat) Dengan Tingkatan Demensia Pada Lansia Kelurahan Bendan Kergon - rizal, m abdur (Universitas Pekalongan, 2018)
Characteristics of respondents based on the age of majority was 65-70 years old as much as 77 respondents (77%), the characteristics of the respondents based on the gender of the majority were women, namely 63 respondents (63%), based on the educational level 51 % of the respondents are uneducated people, based on the characteristics of the majority, respondents are jobless people which of them are 59 respondents (59%). Based on the analysis done on this research, it is found that as many as 41 respondents (41%) are obedient people, and in this research category levels obtained by mild dementia by as much as 75 respondents (75%). The value of the probability (p value) relationship of the level of observance of worship (Salat) and levels of dementia in elderly is 0,291 or p value <0.05.